Circulating CLA+ T lymphocytes as peripheral cell biomarkers in T‐cell‐mediated skin diseases. Issue 7 (25th June 2013) - Ferran, Marta; Romeu, Ester R.; Rincón, Catalina; Sagristà, Marc; Giménez Arnau, Ana M.; Celada, Antonio; Pujol, Ramon M.; Holló, Péter; Jókai, Hajnalka; Santamaria‐BabÍ, Luis F.
Abstract T lymphocytes expressing the CLA antigen constitute a subset of effector memory lymphocytes that are functionally involved in T‐cell‐mediated cutaneous diseases. Skin‐seeking lymphocytes recirculate between inflamed skin and blood during cutaneous inflammation. Many studies in different T‐cell‐mediated inflammatory cutaneous diseases have clearly related their pathologic mechanisms to CLA+ T cells. Based on common features of these cells in different cutaneous disorders mediated by T cells, we propose that circulating CLA+T cells could constitute very useful peripheral cellular biomarkers for T‐cell‐mediated skin diseases.